Oxtiern / Marqués de Sade ; traducción de Álvaro Arauz ; [ilustraciones de Reyes Meza] - Araúz, Álvaro (1911-1970) Reyes Meza, José (1924-); Sade, Marquis de (1740-1814)
Teatro Universal /dirigida por Álvaro Arauz